Model Komunikasi Orang Tua-Anak dengan Kecenderungan Perilaku Seks Pranikah - Nanik Kholifah; Nathania Bayu Astrella (Ilmu Psikologi Universitas Yudharta Pasuruan, 2021)
In various countries, including Indonesia, there are frequent phenomena of premarital sexual behavior. These phenomena do not only occur in big cities even this phenomenon in the village also often happens. Many teenagers who are dating often engage in sexual behavior, so that leaves a lot of unwed, pregnat women. The pourpose of this study to find out if there is a relationship between a parents communication model and premarital sex tendencies. The hypothesis in this study is There is a parental communication model with preeten sexual behavior tendencies. In this study, researchers used a quantitative approach in an effort to test the hypotheses that have been compiled. While the subjects in this study were teenagers in Mojotengah Village, Sukorejo District, Pasuruan Regency. The sampling technique used was purposive sampling. Retrieval of data in this study using a scale model of parent-child communication and the scale of the tendency of premarital sex behavior. Data analysis was calculated by using one predictor regression analysis, and obtained F of 11.971 with p = 0.001. Thus the results of this calculation indicate that there is a significant relationship between communication between the child's parents and premarital sexual behavior.